Correlation Of Nutrition Education On Knowledge Of Anemia And Consumption Patterns Of Tannin In Anemic Adolescent Girls At Smpn 29 Samarinda - Nurmawaddah, Salsabilya; Satriani, Satriani; Novaria, Astri Ayu (Poltekkes Kemenkes Semarang, 2025)
Data from Basic Health Research (Riskesdas) in 2018 showed that the prevalence of anemia in 2018 increased to 48.9%, where the prevalence of SMP/MTS grade VII female students in Samarinda who were at risk of anemia was 7%. Based on the results of interviews with 10 female students, it is known that students have sufficient knowledge of anemia (60%), consume less tannin sources (100%) and do not often consume tannin sources (70%). Anemia can be prevented by providing education that will affect attitudes and food consumption behavior. One of the media that can be used is animated video. This study aims to determine the correlation of nutrition education on knowledge of anemia and consumption patterns of tannin in anemic adolescent girls at SMPN 29 Samarinda. The research design used was pre experimental with a one group pretest posttest design with a sample of 30 female students. The variables studied were nutrition education, knowledge of anemia and consumption patterns of tannin. The instruments used were pretest and posttest questionnaires and SQ-FFQ. The statistical test used is paired T-test if the data is normally distributed and wilcoxon test if the data is not normally distributed or ordinal scale. The results of the wilcoxon test showed that there is an correlation of nutrition education on knowledge of anemia (p=0.000). There is no correlation of nutrition education on the source of tannins consumed (p=0.102) and the frequency of consuming tannins (p=0.808).